Studying Directionality in Simultaneous Interpreting through an Electronic Corpus: EPIC (European Parliament Interpreting Corpus) - Monti, Cristina; Bendazzoli, Claudio; Sandrelli, Annalisa; Russo, Mariachiara (Meta, 2005)
AbstractParallel corpora have long been awaited in simultaneous interpreting studies in order to validate existing theories and models. The present paper illustrates the development of the European Parliament Interpreting Corpus (EPIC), an open, parallel, multilingual (English, Italian and Spanish), POS-tagged corpus of European Parliament source speeches and simultaneously-interpreted target speeches. The aim of the project is to study recurrent lexical patterns and morphosyntactical structures across all the possible language combinations and directions, and verify empirically whether different strategies can be detected when interpreting from a Germanic language into a Romance one and vice-versa, or between two Romance languages. EPIC is freely available on-line for the research community to use and contribute to.